Visual Acuity Gain Profiles and Anatomical Prognosis Factors in Patients with Drug-Naive Diabetic Macular Edema Treated with Dexamethasone Implant: The NAVEDEX Study - Mauricio Pinto; Thibaud Mathis; Pascale Massin; Jad Akesbi; Théo Lereuil; Nicolas Voirin; Frédéric Matonti; Franck Fajnkuchen; John Conrath; Solange Milazzo; Jean-François Korobelnik; Stéphanie Baillif; et al. (MDPI AG, 2021)
The purpose of this study is to evaluate the visual acuity (VA) gain profiles between patients with drug-naive diabetic macular edema (DME) treated by dexamethasone implant (DEX-implant) and assess the baseline anatomical and functional factors that could influence the response to the treatment in real-life conditions. A retrospective, multi-center observational study included 129 eyes with drug-naive DME treated by DEX-implant. The Median follow-up was 13 months. Two groups of VA gain trajectories were identified-Group A, with 71% (n = 96) of patients whose average VA gain was less than five letters and Group B, with 29% (n = 33) of patients with an average gain of 20 letters. The probability of belonging to Group B was significantly higher in patients with baseline VA < 37 letters (p = 0.001). Ellipsoid zone alterations (EZAs) or disorganization of retinal inner layers (DRILs) were associated with a lower final VA (53.0 letters versus 66.4, p = 0.002) but without a significant difference in VA gain (4.9 letters versus 6.8, p = 0.582). Despite a low baseline VA, this subgroup of patients tends to have greater visual gain, encouraging treatment with DEX-implant in such advanced-stage disease. However, some baseline anatomic parameters, such as the presence of EZAs or DRILs, negatively influenced final vision.